Health risk assessment of the heavy metals at wastewater discharge points of textile industries in Tongi, Shitalakkhya, and Dhaleshwari, Bangladesh - Mohsin Uddin; Faisal Bin Alam (Journal of Water and Health, 2023)
Pollution of industry-adjacent surface water bodies has become a major threat to the environment in Bangladesh. This study examined the health risks of concentrated heavy metals in Tongi, Shitalakkhya, and Dhaleshwari, which receive effluents from wastewater treatment plants. Samples were analyzed for heavy metals such as lead, cadmium, iron, magnesium, manganese, zinc, copper, chromium, and nickel. At all the locations, only Zn, Cu, and Ni did not exceed the Bangladesh standard for drinking water. The health risk was estimated using the hazard quotient (HQ) technique. There was a threat of health risks resulting from the exposure through ingestion, with Pb, Cd, Fe, Mg, and Cr being the main contributors. The orders of decreasing values of mean HQ were Mg > Pb > Fe > Cr > Cd, Mg > Fe > Pb > Cr > Cd, and Cr > Mg > Pb > Fe > Cd via oral intake for both adults and children at Tongi, Shitalakkhya, and Dhaleshwari, respectively. For dermal intake, the mean HQ for only chromium at Dhaleshwari exceeded the limit for both groups. The results emphasize the need for enhancement, proper operation, and maintenance of wastewater treatment facilities in order to meet the discharge quality standard. HIGHLIGHTS The river waters in Bangladesh are heavily polluted due to textile wastewater discharge.; Heavy metals such as Pb, Cd, Fe, Mg, and Cr are the main contributors.; The HQ values of Pb, Cd, Cr, Fe, and Mg are higher than 1 for both oral and dermal intake in all sampling locations of the study.; The results indicate a significant level of health risk and a poor state of the wastewater treatment systems employed in the textile industries.;